Wolf man [videorecording (DVD)] - Whannell, Leigh, 1977-; Tuck, Corbett, 1977-; Abbott, Christopher, 1986-; Garner, Julia, 1994-; Firth, Matilda; Hardie, Benedict; Jaeger, Sam; Wallfisch, Benjamin; Duscio, Stefan (Universal, 2025)
Blake, a San Francisco husband and father, inherits his remote childhood home in rural Oregon after his own father vanishes and is presumed dead. With his marriage to his high-powered wife, Charlotte, fraying, Blake persuades Charlotte to take a break from the city and visit the property with their young daughter, Ginger. As the family approaches the farmhouse in the dead of night, they're attacked by an unseen animal and, in a desperate escape, barricade themselves inside the home as the creature prowls the perimeter. Through the night Blake begins to behave strangely, transforming into something unrecognizable, and Charlotte will be forced to decide whether the terror within their house is more lethal than the danger without.